Radiomics Evaluation of Histological Heterogeneity Using Multiscale Textures Derived From 3D Wavelet Transformation of Multispectral Images - Chaddad, Ahmad; Daniel, Paul; Niazi, Tamim (Frontiers in Oncology, 2018)
Purpose: Colorectal cancer (CRC) is markedly heterogeneous and develops progressively towards malignancy through several stages which include stroma (ST), benign hyperplasia (BH), intraepithelial neoplasia (IN) or precursor cancerous lesion and carcinoma (CA). Identification of the malignancy stage of CRC pathology tissues allows the most appropriate therapeutic intervention. Methods: This study investigates multiscale texture features extracted from CRC pathology sections using 3D wavelet transform filter. Multiscale features were extracted from digital whole slide images of 39 patients that were segmented in a pre-processing step using an active contour model. The capacity for multiscale texture to compare and classify between pathology tissues was investigated using ANOVA significance test and random forest classifier models, respectively. Results: 12 significant features derived from the multiscale texture (i.e., variance, entropy, and energy) were found to discriminate between CRC grades at a significance value of p < 0.01 after correction. Combining multiscale texture features lead to a better predictive capacity compared to prediction models based on individual scale features with an average (± standard deviation) classification accuracy of 93.33(± 3.52) %, sensitivity of 88.33 (± 4.12) %, and specificity of 96.89 (± 3.88) %. Entropy was found to be the best classifier feature across all the pathology tissue grades with an average of the area under the curve (AUC) value of 91.17, 94.21, 97.70, 100% for ST, BH, IN and CA, respectively. Conclusion: Our results suggest that multiscale texture features based 3D−WT are sensitive enough to discriminate between CRC grades with the entropy feature the best predictor of pathology grade.